Pengaruh Macam dan Dosis Pupuk Organik terhadap Sifat Agronomi Tanaman Bawang Merah Varietas Bima (Allium ascalonicum L.) - Aji, Restu; Maryani, Yekti; Zamroni (JURNAL ILMIAH AGROUST, 2022)
The purpose of this study was to determine the effect of the type and dose of organic fertilizers, namely cattle pens, goat pens, chicken coops and compost on the yield of the Bima variety of shallots. The research was conducted from January to March 2022 in Bunder Village, Patuk District, Gunung Kidul Regency, D. I. Yogyakarta, with an altitude of 500 meters above sea level, a minimum temperature of 20ºC and a maximum temperature of 33ºC. Rainfall 312.00 mm/year. The experiment in this study consisted of 2 factors, namely the type of organic fertilizer and the dose of organic fertilizer. This study was conducted with 3 repetitions of each factor and arranged in a randomized block design (RBD) so that there were 9 treatment combinations: M1D1, M1D2, M2D1, M2D2, M3D1, M3D2, M4D1, M4D2 and added with 1 control without fertilizer (4x2 ) + 1 = 9. Each experimental unit used 3 sample plants, so that there were 81 sample plants and the total number of plants was 162 plants. The observed variables included plant height, number of leaves per hill, number of plants per hill, plant fresh weight per hill, plant dry weight per hill, tuber diameter, tuber fresh weight per hill, tuber dry weight per hill. Analysis of the results was carried out on the results of observations using variance at the 5% level if there were differences between the treatments tested with the DMRT (Duncan's Multiple Range Test) at the 5% level. There was no interaction between the type and dose of organic fertilizer on the agronomic properties of the shallot variety Bima. The various treatments of organic fertilizers showed no significant difference in the yield of the Bima variety of shallots. The organic fertilizer dose treatment showed that there was a significant difference in the yield of the Bima variety of shallots. Treatment types and doses of organic fertilizers showed no significant differences in control and yield.